ASSOCIATIAON BETWEEN ADROPIN AND ATHEROSCLEROSIS IN HYPERTENSIVE PATIENTS WITH CONCOMITANT TYPE 2 DIABETES MELLITUS AND OBESITY - Shelest, Boris (Medicinski časopis, 2018)
Hypertension (HTN) and diabetes mellitus 2 type (2TDM) are considered as risk factors for atherosclerosis and cardiovascular diseases. Our study suggests that a hormone peptide, called adropin, is involved in the processes of atherosclerotic vessels’ damage in hypertensive patients with T2DM and obesity. As inflammation also suggested being involved in atherosclerosis processes, we studied the IL-6 concentration in enrolled patients. We assessed the links between atherosclerosis intensity and adropin concentration in patients with combination of HTN and 2TDM with obesity. A group of hypertensive patients with 2TDM and obesity (n=99) was prospectively enrolled into the study. The serum IL-6 and adropin levels were measured by ELISA, and the atherosclerosis marker was carotid intima media thickness. Patients were divided on with atherosclerosis (CIMT≥0.9mm) group 1 (n=69), and without atherosclerosis (CIMT<0.9mm) group 2 (n=30). IL-6 level was found to be significantly conversely correlated with serum adropin level only among all enrolled subjects, including control (r=–0,48, P<0.05), but not in the rest of groups. Patients with CIMT≥0.9mm had significantly decreased adropin concentration, and not significantly decreased IL-6 level, comparing with patients with CIMT<0.9mm. Receiver operating characteristic showed that adropin ≤ 1.80 ng / ml was the best cut-off point for differentiating patients with atherosclerosis from a patient without atherosclerosis among hypertensive subjects with concomitant 2TDM and obesity (sensitivity = 76.67%, specificity = 68.12%) In conclusion, a diminished serum adropin concentration was associated with incresed atherosclerosis manifestation, as evidenced by a higher CIMT.